A common fixed point theorm for six expansive mappings in G-metric spaces - Rao, KPR; Sombabu, A; Prasad, J Rajendra (Kathmandu University Journal of Science, Engineering and Technology, 2011)
In this paper we obtain a unique common fixed point theorem for six expansive mappings in G –metric spaces. AMS 2000 Subject classification : 47 H 10; 54 H 25. Key words : Expansive mappings; G –metric space; Weakly compatible mappings DOI: http://dx.doi.org/ 10.3126/kuset.v7i1.5428 KUSET 2011; 7(1): 113-120